CRent: intelligent car rental services for optimised resources and safety in IIUM community - Zainuddin, Ahmad Anwar; Johari, Muhammad Zaid Hazim; Shafie, Mohamad Amir Syakirin; Kamarudin, Saidatul Izyanie; Mohd Khairizam, Ahmad Khairi A'bid (Institute of Nano Optoelectronics Research and Technology (INOR), USM, 2023)
Due to cumbersome procedures, traditional car rental systems fail customers and rental companies. This work presents CRent, a vehicle rental system using mobile app administration and IoT technology. Online car rental platform CRent has an IoT-enabled Accident Detection System (ADS) to improve safety. Online car and financial transactions make rental services effective. ADS alerts owners to occurrences and improves safety. Mobile app management and IoT technology provide real-time tracking, compliance, maintenance, and theft. These improvements enhance rental experiences, whereas 96% of IIUM users and 99% of proprietors supported the proposed scheme. Seat belt and accident detection are already available, and IoT technology will improve the convenience and safety of mobile app-based car rental services. CRent aims to change car renting for consumers and companies. It offers a simple smartphone app for online auto rental, making it accessible to a wide audience. This accessibility can help attract a larger customer base and increase market penetration, leading to increased customer satisfaction.